Difficulty in Management of Advanced Pediatric Orbital Tumor - Nandang Sudrajat; Delfitri Lutfi (Department of Ophthalmology, Faculty of Medicine, Universitas Airlangga, 2021)
Introduction: Tertiary care centers often manage pediatric orbital tumors, especially in advanced lesions and complex management. We report a case of a young boy with a malignant orbital tumor involving intracranial infiltration. Case presentation: A four-year-old boy had proptosis on the left eye for two months accompanied with blurred vision, pain, and oftenly bleeds with ipsilateral nasal congestion. There was no history of trauma, eye disorders, systemic diseases, or growth disorders. The physical examination showed stable vital signs, however a weak general condition and no enlarged regional lymph nodes. Visual acuity of the left eye was no light perception. There was a mass with protrusion of the left eye, swelling of the eyelid with an irregular surface, and a tendency to bleeds. The cornea was hazy with partly scarring, so we could not evaluate the posterior segment. MRI of the head presented a malignant soft tissue mass of the left orbital region with intracranial infiltration. The patient was given adjuvant chemotherapy; however, he could not survive due to systemic complications. Conclusions: The definitive diagnosis for the orbital tumor is obtained by histopathological examination. The investigation with CT scan or MRI imaging could be considered if not possible. However, since the definitive diagnosis still not assessed, the management can be affected. It is essential to have a definitive diagnosis to provide adequate treatment for the patients. Delayed and inadequate management can make malignant orbital tumors potentially life-threatening.